Training in psychiatry throughout Europe - Brittlebank, Andrew (Eur Arch Psychiatry Clin Neurosci, 2016)
Psychiatry is the largest medical specialty in Europe. Despite efforts to bring harmonisation, training in psychiatry in Europe continues to be very diverse. The Union Européenne des Médecins Spécialistes (UEMS) has issued as from 2000 a charter of requirements for the training in psychiatry with an additional European Framework for Competencies in Psychiatry in 2009. Yet these have not been implemented throughout Europe. In this paper, the diversity in training throughout Europe is approached from different angles: the cultural differences between countries with regards to how mental health care is considered and founded on, the cultural differences between people throughout Europe in all states. The position of psychotherapy is emphasised. What once was the cornerstone of psychiatry as medical specialty seems to have become a neglected area. Seeing the patient with mental health problems within his cultural context is important, but considering him within his family context. The purpose of any training is enabling the trainee to gain the knowledge and acquire the competencies necessary to become a well-equipped professional is the subject of the last paragraph in which trainees consider their position and early career psychiatrists look back to see whether what they were trained in matches with what they need in the working situation. Common standard for training and certification are a necessity within Europe, for the benefit of the profession of psychiatrist but also for patient safety. UEMS is advised to join forces with the Council of National Psychiatric Associations (NPAs) within the EPA and trainings and early career psychiatrist, to discuss with the users what standards should be implemented in all European countries and how a European board examination could ensure professional quality of psychiatrists throughout the continent.